موقف الفكر الحداثي من مسائل السمعيات : (دراسة تحليلية نقدية) - حقي، محمد صالح عبد الله
This study aims to shed light on the position of modernist theological dogma about the creed system related to issues of “Sam'iyyat”. It deals with the ontological view about the realities of the day of judgment, such as the resurrection, the account of deeds, the passing through the slippery path (sirat), paradise, and hellfire, as well as other issues such as the torment of the grave, angels, and devils, in which it discusses the different views of modernists with an explanation of the criticism directed at them. However, since modernist thought is wide-ranging, and it is adopted by several thinkers, it became necessary for this study to be linked to selected models in the Arab world, to be closer to the truth. This study has adopted the inductive approach in tracing the texts of the modernists concerning the aspect of audiology by extrapolating their writings and searching for what they said about it. Also, this study relied on the analytical method in approaching their views and evaluating their proofs and evidence. Moreover, this study followed a critical method in critiquing the concept of modernity and the opinions that emerged from it, deconstructing and responding to it according to the scientific method and through rational and textual evidence. This study includes a definition of the key terms of the study, with an indication of the trends of modernism and exploring their theories on metaphysics and their techniques in understanding these metaphysical issues, such as historical and hermeneutical with an explanation of the criticism directed at these methods, as well as discussing their position on the day of judgment and its circumstances. This includes issues related to the resurrection, intersection of the Prophet Muhammad (PBUH), reward and punishment, the measuring of scale, the passing through the slippery path (sirat), paradise and hellfire and countering all these claims. This study found a clear incoherence of modernist thinking in their discussion of the texts of revelation due to their ignorance of the fundamental principles of Shari'ah and the standard methodologies of scrutinizing texts. Not to mention their constant referral to applying tools of western stratagems to the texts, such as historical and hermeneutical approaches and its derivation on the theories of an infinity of meaning and the death of the author, and their attempt in the assumption of the western model of conflict between the churches and scientific revolution, which took on a new understanding of knowledge, that is an alien projection of the Islamic reality and its own temporal and spatial circumstance.